2009
DOI: 10.1002/cphc.200800528
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Platinum on Diffusion Kinetics in β‐NiAl: Implications for Thermal Barrier Coating Lifetimes

Abstract: Platinum is added to thermal barrier coatings (TBCs) as it is observed empirically to extend their lifetime, but the mechanism by which Pt acts is unknown. Since Pt has been proposed to alter diffusivities in NiAl, a key component of TBCs, we use first-principles quantum mechanics calculations to investigate atomic level diffusion mechanisms. Here, we examine the effect of Pt on five previously proposed mechanisms for Ni diffusion in NiAl: next-nearest-neighbor jumps, the triple defect mechanism, and three var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
1
9
1
Order By: Relevance
“…The migration energy of step II, case A represents an upper bound since the Ni atom is actually moving to lattice site that is in close proximity to a periodic image of the Pt atom. We have previously seen that when a Ni or Al atom moves toward a Pt atom, the migration energy increases [5,19], and if the Pt atom was in a different location further from the migrating atom, the migration energy would not Table 4 Al hop starting with the ASB [100] defect cluster 2 in Fig. 2: Defect formation energies (E d ), migration energies (E m ), activation energies (Q), hTST pre-exponential factors (n 0 ); entropic factors and Arrhenius pre-exponential factors (D 0 ) for 1200 K and 1500 K for pure NiAl, and with Pt in site A or site B in Fig.…”
Section: Asb Jumps In (Nipt)almentioning
confidence: 98%
See 2 more Smart Citations
“…The migration energy of step II, case A represents an upper bound since the Ni atom is actually moving to lattice site that is in close proximity to a periodic image of the Pt atom. We have previously seen that when a Ni or Al atom moves toward a Pt atom, the migration energy increases [5,19], and if the Pt atom was in a different location further from the migrating atom, the migration energy would not Table 4 Al hop starting with the ASB [100] defect cluster 2 in Fig. 2: Defect formation energies (E d ), migration energies (E m ), activation energies (Q), hTST pre-exponential factors (n 0 ); entropic factors and Arrhenius pre-exponential factors (D 0 ) for 1200 K and 1500 K for pure NiAl, and with Pt in site A or site B in Fig.…”
Section: Asb Jumps In (Nipt)almentioning
confidence: 98%
“…Table 3 Antistructure bridge mechanism [111] jump: Defect formation energies (E d ), migration energies (E m ), activation energies (Q), hTST pre-exponential factors (n 0 ); entropic factors, and Arrhenius pre-exponential factors (D 0 ) for 1200 K and 1500 K for (a) pure NiAl, (b) with Pt in site A or (c) site B, as depicted in Fig. 4. Step I: [19]. Our earlier work showed that Pt had no effect on the pre-exponential factor to the diffusion constant, so only Pt's effect on activation energies will be discussed here, but the calculated values of the entropic factors (Equation (4)) and pre-exponential factors are presented in Tables 1e3 for completeness.…”
Section: Asb Jumps In (Nipt)almentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, density difference plots (Fig. 4) reveal an increase in electron density around the Pt atom such that a s 2 d 9 -like Pt anion is formed, due to its higher electronegativity (52). In turn, the more diffuse Pt anion destabilizes nearby Ni and Al atoms, favoring Ni vacancy formation in particular.…”
Section: Resultsmentioning
confidence: 97%
“…However, the substantial decreases in the defect formation energies produce large increases in the diffusion rate because these energies appear in the exponential of the diffusion coefficient. Therefore, Pt enhances Ni and Al diffusion by stabilizing the point defects and defect clusters that are intermediate minima along the diffusion pathways (52,55,57).…”
Section: Resultsmentioning
confidence: 99%